PENGARUH DOSIS ROOTONE-F TERHADAP PERTUMBUHAN CROWN TANAMAN NENAS (Ananas comosus) - Ardisela, Dawud (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2010)
Ananas crown can becomes as homogenous plant but longer age than slip and sucker. The result of research show that Rootone-F effect to plant high, amount of leaf, long and widh of leaf sigmificantly at 24 months age especially 100 mg and 200 mg doses treatment. With 400 mg doses show bad effect to plant growing and smaller then control